A novel ginsenoside-hydrolyzing enzyme from Penicillium oxalicum and its application in ginsenoside Rd production. (December 2013) - Gao, Juan; Hu, Yanbo; Ji, Li; Wang, Nan; Wang, Jiao; Tai, Guihua; Zhou, Yifa
Abstract The fungus Penicillum oxalicum can selectively metabolize the major 20(S)-protopanaxadiol ginsenosides Rb1, Rb2, and Rc using extracellular glycosidases yielding a series of bioactive metabolites. A β-glucosidase GH1 was purified from the culture of P. oxalicum with a yield of 9.5% and a specific activity of 3.9 × 103 U/mg. GH1 was a tetramer with a native molecular weight of 484 kDa and its pI value was pH 4.2. GH1 specifically cleaved the β-(1-6)-glucosidic linkage at C-20 site of ginsenoside Rb1 to give the sole product Rd. The optimum conditions were established to be pH 4.5, 55°C, and 0.25 U/ml purified enzyme at 2 mg/ml ginsenoside Rb1. GH1 could be used in the pharmaceutical industry.